1993
DOI: 10.1258/002367793780745624
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme-linked immunosorbent assay (ELISA) for monitoring guineapigs and rabbits for Bordetella bronchiseptica antibodies

Abstract: SummaryAn enzyme-linked immunosorbent assay (ELISA) for monitoring antibodies specific to Bordetella bronchiseptica in guineapigs and rabbits was developed. In conventional and SPF colonies of guineapigs and rabbits, the ELISA was equally successful in detecting infected animals when compared to selective cultivation from the respiratory tract. The ELISA showed a sensitivity of 1000/0 and a specificity of 900/0 in guineapigs. In rabbits the sensitivity and specificity of the ELISA were 97% and 91% respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Furthermore, Jenkins (1977) who tested cross reactivity of ELISA, showed that 2.7% and 13% serum samples from growing pigs and mature hogs, respecively, reacted with Pm antigen. Boot et al (1993) suggested that ELISA be used in cases of monitoring infection caused by Bbr in rabbits and guinea pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Jenkins (1977) who tested cross reactivity of ELISA, showed that 2.7% and 13% serum samples from growing pigs and mature hogs, respecively, reacted with Pm antigen. Boot et al (1993) suggested that ELISA be used in cases of monitoring infection caused by Bbr in rabbits and guinea pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The method of Boot et al [16] was followed to prepare phase I antigen from B. bronchiseptica (MTCC-6838). The stock antigen was diluted 1 : 20 in 0.5% formal saline to OD 269 0.5.…”
Section: Methodsmentioning
confidence: 99%
“…B. bronchiseptica была обнаружена в Японии, Китае, Западной Европе и других странах. В РФ в связи с недостаточностью изучения и условно-патогенной категорией, заболевания кроликов, вызванные данным патогеном, зафиксированы не были [13][14][15][16]…”
Section: результаты и обсуждениеunclassified